FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN PENGODEAN PADA KASUS CEDERA BERDASARKAN ICD-10 DI RUMAH SAKIT KHUSUS BEDAH - Dewi Mardiawati; Linda Handayuni; Ririn Afrima Yenni; Delvia Giovani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: Coding is a classification of a patient's disease, the implementation of which there are still errors both in terms of writing a diagnosis that is unclear to and incomplete. Based on the initial survey conducted, it was found that 15 (75%) of the writing of the diagnosis were unclear, 12 (60%) of the writing of the diagnosis were incomplete, and 14 (70%) incorrect coding of the 20 medical record files. This study aims to determine the accuracy of the coding of injury cases based on ICD-10 at Ropanasuri Hospital, Padang. This research was conducted at the Hospital for Special Surgery Ropanasuri Padang,. The population was 74 medical record files, using the total sampling technique. This research is by means of observation, using a checklist table, the data is processed using a computerized and analyzed by univariate. The results showed that the clarity of writing the diagnosis of injury cases was not clear 49 (66.2%), the completeness of writing the diagnosis of injury cases was incomplete 51 (68.9%), the accuracy of coding the injury cases was not accurate 17 (22.9%). The results of the research on the implementation of coding, especially in injury cases, have been very good where the number of inaccuracies in the code of injury cases is small, but the clarity of writing the diagnosis and completeness of the diagnosis is still not good. Researchers suggest to doctors to improve diagnosis writing and coder to be more active and thorough in coding in order to produce good reporting so as to improve the quality of the hospital.Keywords: Accuracy of coding, Medical Records, ICD-10, Clarity, Completeness